The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1017/jns.2021.48
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and high adherence to the Mediterranean diet in Colombian school children and teenagers during the COVID-19 pandemic according to sex

Abstract: The current COVID-19 pandemic has generated a series of changes in the daily routines of people, including children and teenagers, in an unprecedented way, which constitutes a global challenge in public health. Social isolation has been a prophylactic measure to prevent the spread of the virus, however, it has generated negative impacts on the physical and emotional health of parents, caregivers, children, and teenagers around the world. Our objective was to evaluate the effects of confinement caused by the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
2
0
8
Order By: Relevance
“…Em um momento em que a alimentação deveria dar suporte à saúde, o quadro nutricional, alimentar e comportamental se tornou preocupante. Com o aumento dos fast foods, alimentos fritos e doces, houve a diminuição da aquisição e do consumo de frutas, verduras e legumes (Ruíz-Roso et al, 2020a;Ruíz-Roso et al, 2020b;Morales Camacho et al, 2021;Gomes et al, 2022). Estes comportamentos têm o potencial de impactar negativamente a saúde e a qualidade de vida, persistindo até a fase pós pandêmica ou mesmo na vida adulta (Calabriano et al, 2022).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Em um momento em que a alimentação deveria dar suporte à saúde, o quadro nutricional, alimentar e comportamental se tornou preocupante. Com o aumento dos fast foods, alimentos fritos e doces, houve a diminuição da aquisição e do consumo de frutas, verduras e legumes (Ruíz-Roso et al, 2020a;Ruíz-Roso et al, 2020b;Morales Camacho et al, 2021;Gomes et al, 2022). Estes comportamentos têm o potencial de impactar negativamente a saúde e a qualidade de vida, persistindo até a fase pós pandêmica ou mesmo na vida adulta (Calabriano et al, 2022).…”
Section: Resultsunclassified
“…A qualidade de vida se mostra diretamente relacionada à prática de atividade física e alimentação saudável, influenciando positivamente o bem-estar físico, social e emocional (Nshimirimana et al, 2023). As crianças e os adolescentes experimentaram um impacto negativo em seus estilos de vida devido às consequências diretas da infecção, e indiretos, causado pelo isolamento social (Rocha et al, 2021).…”
Section: Resultsunclassified
“…One study also reported an increase in anxiety and smoking levels (Biviá-Roig et al, 2021). A substantial number of studies reported minimal changes in MD adherence during lockdown (Bagues et al, 2021;Biviá-Roig et al, 2020;Romero-Blanco et al, 2020;Sumalla-Cano et al, 2022;Villodres et al, 2021), while only three studies reported an overall decreased adherence (Di Santo et al, 2020;Marcos-Pardo et al, 2022;Morales Camacho et al, 2021). Of note, all three Spanish randomised-controlled trials that were conducted during lockdown periods reported a significant improvement in participants' dietary habits in the intervention group (García Pérez de Sevilla et al, 2021;Gonzalez-Ramirez et al, 2022;Zaragoza-Martí et al, 2021).…”
Section: Variance In Mediterranean Diet Adherence By Countrymentioning
confidence: 99%
“…En lo que respecta al tema de la nutrición infantil, los productos académicos revisados realizan estimaciones sobre los posibles efectos de la pandemia en la nutrición de los niños y la importancia de contar con políticas y estrategias para mitigar los riesgos. Otros estudios, de carácter empírico, como el realizado por Morales et al (2021) en el municipio Santa Rosa del Sur-Colombia para evaluar los efectos del confinamiento provocado por la pandemia de COVID-19 en los patrones nutricionales, dietéticos y conductuales de niños, "estima una prevalencia de desnutrición, sobrepeso y obesidad en escolares y adolescentes de 10.1, 14.7 y 13.5 %, respectivamente, cifras que resultan ser más altas en comparación con las reportadas en la última encuesta nacional de salud en niños colombianos (ENSIN 2015)" (p.4). El mismo estudio concluye que si bien es cierto los resultados de la investigación no pueden extrapolarse a todas las poblaciones, se observa "una situación nutricional, dietética y conductual preocupante en los niños y adolescentes estudiados durante el confinamiento asociado a la pandemia de COVID-19" Morales et al, 2021, p.…”
Section: Tendencias Nacionalesunclassified